Analyzing Mental Constructs of Communication in Iranian Couples - Yahyapour , Mahtab; Davoodi, Hossein; Jahangiri, Mohamad Mahdi (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of this study is to examine the sources that shape mental constructs in the minds of the participants and their strategies for bringing their own lives closer to that of a successful marriage. Methods: This study employs a qualitative method. Research data were collected through 30 in-depth interviews with 15 Tehranian couples. The data were coded using MAXQDA software, version 2020. The number of participants was determined upon reaching saturation. In the first stage of coding, a total of 860 codes or initial concepts were extracted from the interview transcripts. Findings: The findings of the study indicate that mental constructs of marriage are acquired, modifiable, and constructed entities that are the result of family upbringing and parental relationships, the dominant society and culture, and personal experiences after marriage. The strategies provided by participants for maintaining or achieving a successful marriage amounted to 51 suggestions and strategies, with the highest levels of agreement and recurrence around concepts such as patience, mutual respect, learning problem-solving skills, self-restraint, and communication. Conclusion: This study highlights that mental constructs of successful marriage are shaped by family, lived experiences, and societal influences, emphasizing the importance of empathy, mutual respect, and communication for marital satisfaction and stability.